The Effects Of Accounting Information Systems, Work Motivion, And The Use Of Information Technology On Employee Performace: (An Empirical Study Of Village Administrator Offices Through-out Kubung Subdistrict) - Qurratun Aini; Nidia Anggreni Das; Juita Sukraini (International Journal of Business and Quality Research, 2026)
The purpose of this study is to determine whether the Accounting Information System (X1), Work Motivation (X2), and Information Technology Utilization (X3) affect Employee Performance (Y). The results indicate that the Accounting Information System (X1) affects Employee Performance (Y). The first hypothesis is supported, as the calculated t-value (2.829) > the critical t-value (1.666), and the significance value (0.006) < 0.05. After that, there is an influence of Work Motivation (X2) on Employee Performance (Y). The results of the second hypothesis test indicate that the hypothesis is supported, as evidenced by a calculated t-value of 6.380 > 1.666 and a significance value of 0.000 < 0.05. Therefore, Work Motivation (X2) has a significant effect on Employee Performance (Y). The results of the third hypothesis test are proven by the value of |thitung| of 2.115 > 1.666 and a t significance of 0.038 < 0.05. On the other hand, there are simultaneous effects of the Accounting Information System (X1), Work Motivation (X2), and Information Technology Utilization (X3) on Employee Performance (Y). The results of testing this fourth hypothesis are proven by the |F count| value of 32.584 > 2.73 and the F significance of 0.000 < 0.05.